Criminal Justice Researcher-Practitioner Placement Program: Reading Intervention, Academic and Behavioral Outcomes for Adolescents: A Community Agency and University Partnership Project, Indiana, 2016-2018 - Sander, Janay B. ([Verlag nicht ermittelbar], 2021)
This randomized control trial study aimed to examine whether a targeted reading intervention improved outcomes for juvenile justice involved youth in court-affiliated treatment settings. The data includes reading level assessments at four month intervals and educational, behavioral, and cognitive assessments.